Analisis Perputaran Karyawan (Labour Turnover) Hotel Berbintang Di Kota Jember - Jatmiko, Hadi; Sandy, Syah Riza Octavy (Tourism Scientific Journal, 2024)
This research aims to analyze the labour turnover of Star Hotels in Jember City. The research population was employees of star hotels in Jember City, referring to PHRI Jember data, there were 5 star hotels in Jember City with a total of 162 employees. The sample for this research was some employees of star hotels in Jember City. The sampling method used was the quota sampling method, namely a predetermined/rationed sample collection method. The sample size was determined at 60 respondents, which was based on the rule that the sample size was at least 15 times the variables. Structured interviews with hotel managers and management associations. The data analysis technique used in this research is multiple linear regression. Result of statistical analysis shows that the compensation factor variable has a negative and significant effect on labour turnover, the career path variable has a negative and significant effect on labour turnover, the work stress variable has a positive and significant effect on labour turnover.